Robot Control on the basis of Bio-electrical signals - Ierache, Jorge Salvador (2009)
This article shows the experiences carried out in the context of human/robot communication, on the basis of brain bio-electrical signals, with the application of the available technologies and interfaces which have facilitated the reading of the user’s brain bio-electrical signals and their association to explicit commands that have allowed the control of biped and mobile robots through the adaptation of communication devices. Our work presents an engineering solution, with the application of technological bases, the development of a high- and low-level communication framework, the description of experiments and the discussion of the results achieved in field tests.